Needs analysis fo the development of web-based teaching materials in scientific writing skills instruction for eleventh-grade vocational high school students - Susanti, Evi; Hikmat, Ade; Tarmini, Wini (Universitas Ahmad Dahlan, 2025)
The development of students' scientific writing skills remains a significant challenge in vocational high schools, where conventional teaching materials often fail to accommodate students' technological learning preferences. This study aims to analyze the needs for developing web-based teaching materials to enhance the scientific writing skills of eleventh-grade vocational students. Utilizing a Research and Development (R&D) approach with the ADDIE model framework, this study involved two vocational school teachers and sixty eleventh-grade students in Bandung, Indonesia. Data were collected through teacher interviews and student questionnaires, then analyzed descriptively. The findings revealed that 63% of students experienced difficulties in scientific writing due to limited understanding of formal writing techniques, structuring arguments, and lack of digital learning resources. Teachers indicated the necessity for contextualized and interactive web-based learning platforms that align with the differentiated learning approach of the Curriculum Merdeka. Furthermore, over 80% of students expressed a preference for digital and interactive learning environments to improve their engagement and writing competence. The study concludes that the development of web-based portable-E teaching materials is essential to bridge the gap between students' needs and current teaching practices. The proposed innovation not only addresses students' difficulties in writing but also promotes independent learning, enhances digital literacy, and supports the achievement of curriculum goals. These findings offer valuable insights for future instructional material design and educational technology integration in vocational education contexts.